Two-year summary: four hybrid sorghum grains fed in all-concentrate rations to steers - McCollough, R.L.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
This station has grown and fed the same four (yellow endosperm) hybrid sorghum grains (Funk G-766W, Acco R-l09, DeKalb E-57, and Northrup King 222) in an all-concentrate ration to steers two consecutive years. Results are summarized here.
Keywords: Beef; Hybrid sorghum grain; Steers